The Lord's Prayer - Black, C. Clifton 1955- (Louisville, Kentucky Westminster John Knox Press, 2018)
Pt. 1. Getting our bearings. The religious world of the Lord's Prayer -- Prayer in the Gospels -- Pt. 2. Interpreting the prayer: the first table. Our heavenly Father -- The consecrated name -- Kingdom and will -- Pt. 3. Interpreting the prayer: the second table. Bread -- Debts and forgiveness -- Rescue from ultimate danger and evil -- Pt. 4. Doxology and conclusion. Kingdom, power, and glory -- A pastoral coda.
C. Clifton Black provides a thorough analysis of the most famous prayer in the Christian church, the Lord’s Prayer. He begins with an impressionist painting of how the ancients prayed during Jesus’ time in order to set the context for understanding the prayer he taught his disciples. Throughout the book, Black systematically interprets the rich meanings of each part of the Lord’s prayer. Additionally, he includes an overview of Christian thought on the Lord’s Prayer from early church mothers and fathers like Tertullian and Teresa of Avila to modern theologians like Karl Barth. Uniquely, this book is an academic study of the Lord’s Prayer with a focus on the rhetorical culture from which it developed as well as the theological, literary, and historical meanings of the prayer itself
Includes bibliographical references and indexes
Keywords: Lord's Prayer -- Criticism, interpretation, etc